Application of Baduanjin qigong exercise for community-based group of elderly individuals with chronic nonspecific low back pain (中医气功八段锦干预社区老年慢性非特异性下腰痛患者的效果分析) - LI Juan (栗娟); BAI Jianying (白建英); LI Jie (李洁); SHEN Yongqing (沈永青); QI Suwen (戚素文); FENG Huiling (冯会玲) (中西医结合护理)
Objective The aim of this study was to assess the effectiveness of the Baduanjin qigong exercise on chronic nonspecific low back pain in community-based group of elderly population. Methods Totally 76 patients with chronic nonspecific low back pain were randomly divided into the experimental group(n=37)and the control group(n=39). The control group received routine care and health education about chronic nonspecific low back pain, and the experimental group received Baduanjin qigong exercise additionally. The primary and secondary outcomes measures of this trial were pain intensity and back functional disability. The Visual Analogue Scale (VAS) and the Oswestry Disability Index (ODI) questionnaires were used to obtain data, which were measured respectively before intervention and three months later. Results Patients in the experimental group had a greater improvement than the controls in VAS scores after a 12-week intervention of Baduanjin exercise(P＜0. 01). The total score of ODI , dimensional scores of Lifting, Walking and Social Life in the experimental group were lower than those in the control group(P＜0. 05) . Conclusion Baduanjin qigong exercise appears to be slightly to moderately effective on relieving pain and improving function. (目的 探讨运用中医气功八段锦运动干预社区老年慢性非特异性下腰痛患者的效果。方法 将76例慢性非特异性下腰痛患者随机分为对照组和试验组, 对照组39例患者给予慢性非特异性下腰痛常规护理和健康教育, 试验组在对照组基础上进行中医气功八段锦运动干预。分别在干预前、干预12周后采用视觉模拟量表(VAS)和Oswestry功能障碍指数(ODI)问卷评价患者的疼痛程度和腰部功能情况。结果 干预12周后, 两组疼痛程度均较干预前下降, 且试验组疼痛程度低于对照组, 差异有统计学意义(P＜0. 01)。干预12周后, 试验组ODI总分及提物、步行、社会生活条目得分低于对照组, 差异有统计学意义(P＜0. 05)。结论 中医气功八段锦运动干预可有效缓解老年慢性非特异性下腰痛患者的腰部疼痛, 改善腰部功能。)